SIP construction with EPS and galvanised electro-welded mesh - Waseem Shah, Muhammad; Waseem Shah, Syeda Sumera (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
SIP stands for structure insulated panels which is usually constructed of oriented strand boards (OSB) on the interior and exterior sides with foam like Expanded polystyrene (EPS), extruded polystyrene (XPS) or rigid poly-urethane foam, sandwiched in between the OSB sheets. Around the polystyrene; plywood, pressure treated plywood, aluminium, thin mesh of steel, stainless steel etc can also be used in replacement to OSB panels. This article focus on a new idea which is using polystyrene sheets 170mm thick, 2.4m long and 1.2m wide with 3mm electro-welded mesh on both faces with both main and distribution bars. Depending on the loading the spacing can be reduced and some extra bars at length L/3 can be welded to the mesh. The SIP with galvanized electro-welded mesh acts like RC structure and if installed by trained persons it is suitable for all design loads as all the factory tests have been conducted on them. The advantages of using SIP panels with electro-welded mesh are easy to install, economical (at least half a price of traditional build), speedy construction (takes about half of the time as compared to traditional build), light weight, fire resistant, flexibility, thermal properties, easy transportation etc.